Student Satisfaction and Priority Quadrants towards E-Learning - Rr Rachmawati; Yunia Mulyani Azis; Moechammad Sarosa (Universitas Pendidikan Ganesha, 2023)
The e-learning learning method has long been known in distance learning and is increasingly being used during a pandemic, especially during an endemic period like today. Students who are accustomed conducted face-to-face learning as a cause of low learning outcomes. Several studies using multiple linear regression analysis have concluded that the level of student satisfaction with the e-learning learning model has an effect on learning outcomes. Additional analytical methods are needed to measure the quality of e-learning services and at the same time be able to make priority scales for handling them. The purpose of this study was to analyze the partial and simultaneous effect of service equal on student satisfaction in the e-learning method, measure the level of student satisfaction and make a priority scale for handling it. The subjects were 100 students who took MSDM courses. The research method used observation, literature studies related to service quality regarding e-learning quality. Data analysis was done by calculating the difference between the average values of reality and expectations for each service quality attribute. The result found that (1) partially the reliability variable is the variable that has the most influence, while the assurance variable is the variable that has the least effect on student satisfaction, (2) the tangible variable has no effect on satisfaction, and (3) the attributes that are the priority improvement is the attribute of the timeliness of teaching and the teacher providing explanations (guidelines) on the learning materials and the use of the e-learning platform.